COMPARISON OF SINGLE DOSE AND THREE DOSE ANTIBIOTIC PROPHYLAXIS WITH CEFOTAXIME SODIUM IN CHOLECYSTECTOMY - Zahid, M. A.; Bakhsh, Rasool; Dar, Faisal Saud; Akhter, Noor; Malik, Zafar Iqbal (Journal of Ayub Medical College Abbottabad, 2003)
Background: This study was conducted in Surgical Unit-I at Pakistan Institute of Medical Sciences (PIMS), Islamabad from October 2000 to March 2002. The objective of the study was to compare the results of single dose versus three-dose prophylaxis by cefotaxime sodium in patients undergoing elective cholecystectomy. Method: Intravenous Cefotaxime sodium as a prophylaxis was used in 150 patients who underwent elective cholecystectomy. Half of the patients were given single dose one hour before surgery (Group A) while the other half (Group B) was given three doses, first one hour before surgery, second and third were given at 8 hour interval after surgery. Postoperative hospital stay of all but two patients was not more than three days. Evidence of wound infection was observed for 4 weeks post-operative in surgical out patient department in both groups. Results: Three patients in group A and four in group B got wound infection. The difference was not statistically significant. Conclusion:Single preoperative dose can be recommended in cholecystectomy as it is less costly and has the same prophylactic benefits as of single dose. Keywords: Antibiotic Prophylaxis, Cefotaxime